1999
DOI: 10.1023/a:1008336415362
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstanding in cancer patients: Why shoot the messenger?

Abstract: SummaryAim: We aimed to document the prevalence of misunderstanding in cancer patients and investigate whether patient denial is related to misunderstanding.Patients and methods: Two hundred forty-four adult cancer outpatients receiving treatment completed a survey assessing levels of understanding and denial. Doctors provided the facts against which patient responses were compared. Multiple logistic regression analyses determined the predictors of misunderstanding.Results: Most patients understood the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
144
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 29 publications
(33 reference statements)
12
144
0
3
Order By: Relevance
“…The impact of treatment on patient's quality of life was discussed in only onethird of consultations, and oncologists checked for patient understanding of information in only 10%. Even when all relevant information is discussed with their oncologists, as many as a third of patients misunderstand this information (Gattellari et al, 1999). This should not surprise oncologists, given the amount and complexity of information to review, the anxiety and distress associated with a diagnosis of advanced cancer and possible coping strategies, such as denial.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of treatment on patient's quality of life was discussed in only onethird of consultations, and oncologists checked for patient understanding of information in only 10%. Even when all relevant information is discussed with their oncologists, as many as a third of patients misunderstand this information (Gattellari et al, 1999). This should not surprise oncologists, given the amount and complexity of information to review, the anxiety and distress associated with a diagnosis of advanced cancer and possible coping strategies, such as denial.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Distress and denial are known to reduce the amount of information patients retain after conversations with physicians. 50,51 Data from the Australian and American contexts have shown that age and gender do not appear to be significant factors in comprehension, but patients who have not completed secondary school and for whom English is a second language are less likely to have concordance with their physician. 51,52 Physicians may overestimate patient understanding, 53 and Australian oncologists have been reported to seek confirmation of understanding in only 10% of consultations.…”
Section: How Patients Interpret What Is Saidmentioning
confidence: 99%
“…50,51 Data from the Australian and American contexts have shown that age and gender do not appear to be significant factors in comprehension, but patients who have not completed secondary school and for whom English is a second language are less likely to have concordance with their physician. 51,52 Physicians may overestimate patient understanding, 53 and Australian oncologists have been reported to seek confirmation of understanding in only 10% of consultations. 35 Patients may be reluctant to ask for clarification, particularly when there is a language barrier.…”
Section: How Patients Interpret What Is Saidmentioning
confidence: 99%
“…Many patients do not discuss their prognosis or concerns regarding end-of-life care with their doctor or family [3][4][5]. Lack of such discussions and sub-optimal communication can contribute to poor decision-making and outcomes at the end-of-life.…”
Section: Introductionmentioning
confidence: 99%